Accuracy of brain computed tomography interpretation by internists at emergency room after official hour periods in HRH Princess Maha Chakri Sirindhorn Medical Center - Amornvittayachan, Ornsiri; Torwarapanit, Mattana; Supparojpattana, Pichai; Varavithya, Vithya (Journal of Medicine and Health Sciences, 2014)
Accurate initial interpretations of brain computed tomography scan (CTs) by internists and primary care physicians remain critical in decision-making and the resulting quality of care. To determine the accuracy of interpretation of brain CTs by internists in radiology department after official hour periods at the HRH Princess Maha Chakri Sirindhorn Medical Center in Nakhon Nayok, Thailand. Between January 2011 and December 2012, 125 brain CTs imagings were requested, initially interpreted by internists and reviewed by 2 experienced radiologists. Compared interpretation results were calculated. Accurate percentages of brain CTs interpretation in ischemic stroke, intracranial hemorrhage, skull or facial fracture, intracranial mass, hydrocephalus, and brain herniation were 80.8%, 91.2%, 96.8%, 99.2%, 92%, and 92.8%, respectively. The numbers of patients in agreement interpretation were 83 (66.4%) in the agreement (AG) group, 27 (21.6%) in the disagreement significant (DS) group, and 15 (12.0%) in the disagreement insignificant (DI) group. Most interpretations of brain CTs done by the internists had shown a poor sensitivity but a high specificity. In conclusion, low accuracy of brain CTs interpretations by internists after official hour were in cases of ischemic stroke. Education in brain CTs interpretations for internists is necessary for improving the quality of treatment. ความแม่นยำ ของการแปลผลเอกซเรย์ คอมพิวเตอร์สมองของแพทย์เพิ่มพูนทักษะ ณ ห้องฉุกเฉินช่วงนอกเวลาราชการ โรงพยาบาลศูนย์การแพทย์สมเด็จพระเทพฯ ความแม่นยำของการแปลผลเอกซเรย์คอมพิวเตอร์สมองของผู้ป่วยเบื้องต้นมีความสำคัญมากและส่งผลต่อคุณภาพ การดูแลรักษาผู้ป่วยเบื้องต้นโดยเฉพาะช่วงนอกเวลาราชการซึ่งแพทย์ส่วนใหญ่ที่ดูแลคือ แพทย์เพิ่มพูนทักษะ การศึกษานี้ มีวัตถุประสงค์เพื่อทำการประเมินความแม่นยำของการแปลผลเอกซเรย์คอมพิวเตอร์สมองโดยแพทย์เพิ่มพูนทักษะในช่วง นอกเวลาราชการ โรงพยาบาลศูนย์การแพทย์สมเด็จพระเทพฯ ในช่วงมกราคม 2553 ถึงธันวาคม 2555 พบว่ามีการตรวจ เอกซเรย์คอมพิวเตอร์สมอง 125 ครั้ง ซึ่งถูกแปลผลโดยแพทย์เพิ่มพูนทักษะ หลังจากนั้นภาพดังกล่าวจะถูกอ่านทบทวนโดย รังสีแพทย์ที่มีประสบการณ์ 2 ท่าน เมื่อเปรียบเทียบผล พบว่าความแม่นยำของการแปลผลเอกซเรย์คอมพิวเตอร์สมองใน หมวดหมู่ภาวะเส้นเลือดสมองตีบ เลือดออกในสมอง กระดูกกะโหลก และกระดูกใบหน้าแตกร้าว ก้อนเนื้องอกในสมอง น้ำคั่งในโพรงสมองและสมองเลื่อน เป็นร้อยละ 80.8,91.2,96.8,99.2,92 และ 92.8 ตามลำดับ และความเห็นในการเเปลผล เอกซเรย์คอมพิวเตอร์สมองโดยแพทย์เพิ่มพูนทักษะซึ่งถูกอ่านทบทวนโดยรังสีแพทย์พบว่ามีความเห็นตรงกัน ความเห็นไม่ ตรงกันอย่างมีนัยสำคัญ และความเห็นไม่ตรงกันอย่างไม่มีนัยสำคัญ เป็นร้อยละ66.4,21.6และ12ตามลำดับ และพบว่าใน ภาพรวมการแปลผลเอกซเรย์คอมพิวเตอร์สมองมีความไวค่อนข้างต่ำแต่มีความจำเพาะค่อนข้างสูง สรุปว่าความแม่นยำของ การแปลผลเอกซเรย์คอมพิวเตอร์สมองโดยแพทย์เพิ่มพูนทักษะช่วงนอกเวลาราชการมีค่าต่ำที่สุดคือ ภาวะเส้นเลือดสมองตีบ และมีค่าสูงที่สุดคือ ก้อนเนื้องอกในสมอง การให้ความรู้ในการอ่านแปลผลภาพเอกซเรย์คอมพิวเตอร์สมองจึงมีความสำคัญ เพื่อปรับปรุงคุณภาพการรักษา